Design in Operational Projects - Two, ITM-OM Team; Sorooshian, Shahryar; Adham, Ali Asghar Jomah (Journal of Management and Science, 2013)
This paper is a brief review article to study current studies in good and service design, for a class activity in Operations management tutorial under University Malaysia Pahang Undergraduate Programs. In this paper a team of students as their tutorial work studied researches to find what the role of manager of good and service designis.